Duration and key determinants of infectious virus shedding in hospitalized patients with coronavirus disease-2019 (COVID-19) - van Kampen, Jeroen J. A.; van de Vijver, David A. M. C.; Fraaij, Pieter L. A.; Haagmans, Bart L.; Lamers, Mart M.; Okba, Nisreen; van den Akker, Johannes P. C.; Endeman, Henrik; Gommers, Diederik A. M. P. J.; Cornelissen, Jan J.; Hoek, Rogier A. S.; van der Eerden, Menno M.; et al. (Nature communications, 2021)
Key questions in COVID-19 are the duration and determinants of infectious virus shedding. Here, we report that infectious virus shedding is detected by virus cultures in 23 of the 129 patients (17.8%) hospitalized with COVID-19. The median duration of shedding infectious virus is 8 days post onset of symptoms (IQR 5–11) and drops below 5% after 15.2 days post onset of symptoms (95% confidence interval (CI) 13.4–17.2). Multivariate analyses identify viral loads above 7 log 10 RNA copies/mL (odds ratio [OR] of 14.7 (CI 3.57-58.1; p < 0.001) as independently associated with isolation of infectious SARS-CoV-2 from the respiratory tract. A serum neutralizing antibody titre of at least 1:20 (OR of 0.01 (CI 0.003-0.08; p < 0.001) is independently associated with non-infectious SARS-CoV-2. We conclude that quantitative viral RNA load assays and serological assays could be used in test-based strategies to discontinue or de-escalate infection prevention and control precautions. Duration of infectious SARS-CoV-2 shedding is an important measure for improved disease control. Here, the authors use virus cultures of respiratory tract samples from COVID-19 patients and observe a median shedding duration of 8 days and a drop below 5% after 15,2 days post onset of symptoms.